Accelerator‐free gloves as alternatives in cases of glove allergy in healthcare workers. (27th July 2017) - Crepy, Marie‐Noëlle; Lecuen, Jérome; Ratour‐Bigot, Carole; Stocks, Jill; Bensefa‐Colas, Lynda
Summary: Background: Accelerators in rubber gloves constitute an important group of contact allergens, particularly in healthcare workers. Objectives: To assess the efficacy of accelerator‐free medical gloves in the secondary prevention of allergic contact dermatitis caused by rubber accelerators in healthcare workers. Methods: Nine healthcare workers with hand eczema were advised to use accelerator‐free rubber gloves after a diagnosis of allergic contact dermatitis caused by rubber accelerators. Results: Switching from conventional medical single‐use gloves containing accelerators to accelerator‐free medical gloves led to improvement in all cases, and more than two‐thirds of the patients were completely free of symptoms. Conclusion: The use of accelerator‐free medical gloves can be an effective alternative in healthcare workers who are allergic to rubber accelerators.